Advanced mechanics of composite materials and structural elements - Vasiliev, Valery V.; Morozov, Evgeny V. (Elsevier, 2013)
Analyzes contemporary theoretical models at the micro- and macro levels of material structure. This title includes its coverage of practical methods and approaches, experimental results, and optimization of composite material properties and structural component performance that can be put to practical use by researchers and engineers